Analisis Tingkat Kepuasan Konsumen Terhadap Produk Kandang Kelinci UMKM Dandellion Menggunakan Metode Kano - Abu Ayyub Al Anshari; Ferida Yuamita (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
UMKM Dandellion is a business engaged in rabbit farming and sells various kinds of rabbit livestock needs ranging from feed, vitamins, medicines and rabbit cages. In running its business, UMKM Dandellion applies a pre order system for ordering cages, especially rabbit cages, in carrying out rabbit cage production activities, UMKM Dandellion finds delays in making cages due to the availability of stock materials from suppliers which can cause customer satisfaction levels. Therefore, the purpose of this study is to analyze the level of customer satisfaction with cages using the kano method, from the results of the research conducted, it is said that there are 8 question attributes in the Attractive category and 4 question attributes in the Must-be category.